Comparative study of film forming behaviour of low and high amylose starches using glycerol and xylitol as plasticizers - Muscat, D.; Adhikari, B.; Adhikari, R.; Chaudhary, Deeptangshu (Elsevier Science, 2012)
In this study, the film forming behaviour of low amylose (LA) and high amylose (HA) starches was studied. The starch-alone and a blend of plasticizer (polyol)–starch films were developed by gelatinising at various temperatures and casting at 25 °C. The starch–plasticizer films contained glycerol and xylitol either individually or in 1:1 combination. The concentration of plasticizer used was 15%, 20% and 30% for LA films while it was 20%, 30% and 40% for HA films on dry solid basis. The HA-glycerol films retained the highest moisture content among all the films. The HA films exhibited higher glass transition temperature, higher tensile strength, higher modulus of elasticity and lower elongation at break than those obtained from LA starch. The tensile strength and modulus of elasticity decreased and the elongation increased with increasing plasticizer concentrations above 15% on dry solid basis regardless the starch type. Low water vapour permeability was evident in LA and HA films plasticized by combined plasticizers at 20% plasticizer concentration. Rheological measurements showed that most of the suspensions exhibited Herschel–Bulkley behaviour and some of the HA suspensions exhibited Bingham plastic behaviour. At 15% (on dry solid basis) plasticizer concentration, the films obtained from both the starches were brittle due to the anti-plasticization behaviour.